West Java DPRD Political Communication in the Policy of Religious Tolerance - Abdullah S. Haris Sumadiria; Mahi Mamat Hkikmat (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2022)
Along with the times, the implementation of tolerance must continue to increase, starting with growing knowledge and implementing it. Among these elements are members of the legislature who have policies that play a significant role in political communication with their constituents. This study aims to examine the knowledge of DPRD members in the West Java region regarding religious tolerance, the political communication of DPRD members in the West Java region regarding religious tolerance policies, and formulate a model of political communication carried out by DPRD members in the West Java region in a policy of religious tolerance. Using qualitative research methods, this study used interview data collection techniques. The conclusion is that DPRD members in the West Java region have extensive knowledge about religious tolerance, the political communication of DPRD members in the West Java region is quite complete involving internal and external political communication, and the model of political communication developed is making regional regulations, monitoring, and creating rules budgeting for religious tolerance programs. The impact of the research results is expected to increase religious tolerance in the West Java region and inspire DPRD members in other areas to increase knowledge and political communication regarding religious tolerance.